Clinical and Economic Evaluation of Salvianolate Injection for Coronary Heart Disease: A Retrospective Study Based on National Health Insurance Data in China - Yang, Lisong; Chen, Xiaolan; Oi Lam Ung, Carolina; Zhu, He; Hu, Hao; Han, Sheng (Frontiers in Pharmacology, 2020)
Objective: The study aimed to conduct clinical and economic evaluation of salvianolate injection for patients with coronary heart disease (CHD) in comparison to Danhong injection and alprostadil injection. Method: This was a retrospective study using National Health Insurance Data about inpatients diagnosed with CHD in China in 2015 who met the inclusion criteria. The recruited patients were divided into two samples: surgery and non-surgery. The exposed group received salvianolate injection, while the control group received either alprostadil injection or Danhong injection. The medical cost per hospitalization, hospitalization duration, and the rehospitalization rates were used as outcome indicators. Heterogeneity was processed according to disease stratification. Propensity score matching and multivariate analysis were used for statistical analysis to control potential confounding factors. Results: The hospitalization duration of salvianolate injection group was significantly (P < 0.05) shorter than that of Danhong injection group in the non-surgery sample. The hospitalization duration of salvianolate injection group was significantly (P < 0.05) shorter than those of alprostadil injection group in both surgery and non-surgery samples. In the non-surgery sample, the medical cost per hospitalization of salvianolate injection group was significantly (P < 0.05) lower than that of alprostadil injection group. However, there were no statistical differences of rehospitalization rates in salvianolate injection group vs. alprostadil injection group or salvianolate injection group vs. Danhong injection group in both surgery and non-surgery samples. Conclusion: Salvianolate injection showed advantages in reducing hospitalization duration for inpatients with CHD when comparing with alprostadil injection and Danhong injection. The results of this real-world study can help to inform clinical practice for CHD patients.